This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: we have a x = 0 and a y = -g, giving the kinematic equations: v x = v 0x + a x t → v x = v 0x x = x + v 0x t +½ a x t 2 → x = x + v 0x t v y = v 0y + a y t = v 0x → v y = v 0y- g y t y = y + v 0y t +½ a y t 2 → y = y + v 0y t -½ gt 2 v y 2 = v 0y 2 + 2a y (y - y ) → v y 2 = v 0y 2 – 2g(y - y ) Relative Motion: Consider an object moving with velocity, bs v , relative to a surface, where this surface in turn moves with a velocity, se v , relative to the earth. The velocity of this body, be v , relative to the earth, is then given by the relation: se bs be v v v + = Phsx114 – sp07-Formula Sheet for Exam 1, Page 2 of 2...
View Full Document
- Spring '08
- Equations, Quadratic equation, Elementary algebra